Optimizing talent and succession for organizational achievement - Hasman Budiadi; Muhammad Hasbi; Setiyowati Setiyowati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines talent management and succession planning in the leadership cadre process of the Prosperous Justice Party (PKS) as strategic efforts to ensure leadership continuity and organizational performance. Using a qualitative phenomenological approach, the research focuses on the Central Leadership Council and the Syuro Assembly of PKS. The findings reveal that PKS implements a structured talent management model consisting of six phases: criteria determination, cadre development, Development Center Group selection, accelerated development, key position assignment, and program evaluation. Succession planning is carried out through eight stages, including high-level deliberation, responsibility allocation, needs assessment, professional development, individual focus, position expansion, election, and evaluation. These processes are guided by the party’s vision, AD/ART, and succession as a preparatory mechanism. The study highlights a strong interrelationship between talent management and succession planning, where talent management prepares leadership candidates, and succession outcomes inform future talent criteria. Overall, the model ensures the availability of qualified cadres ready for future leadership roles.